Blended learning, Edmodo, physical education, health and sports, short distance running - Fadil, Arifka; Pelana, Ramdan (Program Pascasarjana Universitas Negeri Jakarta, 2023)
Education is one of the areas that technology seeks to achieve through online learning. Online learning is indeed less effective because most of it causes problems both from the point of view of students. The blended learning method of learning is a form of learning system that combines online and offline systems that are applied in learning physical education, health and sports. The purpose of this research is to prove the phenomenon of technological advancement in the rapidly growing world of education and data that supports the progress of student learning, that blended learning can be used for modern learning solutions, so that students can study material before practice in the field to increase teaching achievement. The results of this study indicate that blanded learning based on edmodo can improve learning outcomes for short distance running can be seen from, the increase in learning outcomes in the pre-test shows students who complete 9 students, the increase occurs in cycle 1 to 20 students and continued at the stage of cycle 2 has increased results 25 students completed.